1977
DOI: 10.1002/app.1977.070210402
|View full text |Cite
|
Sign up to set email alerts
|

Electron diffraction technique for the determination of cellulose crystallinity

Abstract: SynopsisAn electron-microscopic diffraction technique has been described to record with ease diffraction patterns of cotton cellulose with 3-5 sec exposure time, which is suited to determine the crystallinity of cellulose. The % crystallinity index for cotton and ramie determined by this technique amounted to 81% and 85%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The patterns indicate very high orientation of cellulose crystals in the fibres. They are similar to that of jute fibres (Lin et al 2014), ramie fibre (Woodcock & Sarko 1980) and also electron diffraction patterns of ramie (French 1978) and cotton microfibrils (Herbert & Muller 1974;Paralikar & Betrabet 1977) suggesting that the cellulose in PALF is of type 1 (Cellulose I). This is characterized by the three diffractions assigned (110), (200), and (004).…”
Section: Waxs Analysis Of Fibre Bundles and Microfibressupporting
confidence: 68%
“…The patterns indicate very high orientation of cellulose crystals in the fibres. They are similar to that of jute fibres (Lin et al 2014), ramie fibre (Woodcock & Sarko 1980) and also electron diffraction patterns of ramie (French 1978) and cotton microfibrils (Herbert & Muller 1974;Paralikar & Betrabet 1977) suggesting that the cellulose in PALF is of type 1 (Cellulose I). This is characterized by the three diffractions assigned (110), (200), and (004).…”
Section: Waxs Analysis Of Fibre Bundles and Microfibressupporting
confidence: 68%
“…The electron diffraction (ED) patterns from these crystals were recorded using the method described earlier. 17 The d spacings of the reflections were measured.…”
Section: Methodsmentioning
confidence: 99%
“…The cellulase blends from P. funiculosum and T. harzianum were concentrated as described in Section 2. amorphous part of the cellulose would be depolymerized first, which increases the crystallinity of the cellulose during enzymatic hydrolysis [26,27]. However, several research groups have found that crystallinity does not increase during enzymatic hydrolysis [28][29][30][31].…”
Section: Crystallinity Of Lignocellulose Samplesmentioning
confidence: 99%